Effectiveness of Egg Stimulant® and Oodev® for Maturation of Tilapia (Oreochromis niloticus) - PB, Andre Ramadhan; Sarida, Munti; Adiputra, Yudha Trinoegraha (Jurnal Perikanan dan Kelautan, 2021)
Lack of distribution, inbreeding depression and environment factors were several negative impacts to tilapia fry quality. It is needed to enhance fry quality by increasing reproduction performance of broodstocks with nutrient and hormonal by using Egg stimulant® and Oodev®. This research purposed to evaluate maturation process with Egg stimulant and Oodev application and effective doses to increase reproduction performance of female tilapia broodstocks. This research conducted within two months at Unit Pelaksana Teknis Dinas Perikanan Budidaya Air Tawar (UPTD PBAT) Wilayah Barat Tanggamus. The research design used was a complete randomized designs two factors and two levels with three replications. Control treatment (K) (Egg stimulant feed 0 g/kg and Oodev injection 0 ml/kg), P1 (Egg stimulant feed 3 g/kg), P2 (Oodev injection 0,5 ml/kg) and P3 (Egg stimulant feed 3 g/kg and Oodev injection 0,5 ml/kg) The results showed that P1, P2 and P3 treatments were not significantly different to eggs diameter, gonadal maturation level, gonadal maturation index, relative fecundity, and fertilization rate. However, Egg stimulant and Oodev were functionally enhance reproduction performances of female tilapia broodstock.  It is showed by treatments has better result than control.  The effective doses of Egg stimulant, Oodev or combination need more longer period of research to applying in tilapia husbandry